Creation of system of computer-aided design for technological objects - Zubkova, T M; Tokareva, M A; Sultanov, N Z (Journal of physics. Conference series, 2018)
Due to the competition in the market of process equipment, its production should be flexible, retuning to various product configurations, raw materials and productivity, depending on the current market needs. This process is not possible without CAD (computer-aided design). The formation of CAD begins with planning. Synthesizing, analyzing, evaluating, converting operations, as well as visualization and decision-making operations, can be automated. Based on formal description of the design procedures, the design route in the form of an oriented graph is constructed. The decomposition of the design process, represented by the formalized description of the design procedures, makes it possible to make an informed choice of the CAD component for the solution of the task. The object-oriented approach allows us to consider the CAD as an independent system whose properties are inherited from the components. The first step determines the range of tasks to be performed by the system, and a set of components for their implementation. The second one is the configuration of the selected components. The interaction between the selected components is carried out using the CALS standards. The chosen CAD / CAE-oriented approach allows creating a single model, which is stored in the database of the subject area. Each of the integration stages is implemented as a separate functional block. The transformation of the CAD model into the model of the internal representation is realized by the block of searching for the geometric parameters of the technological machine, in which the XML-model of the construction is obtained on the basis of the feature method from the theory of image recognition. The configuration of integrated components is divided into three consecutive steps: configuring tasks, components, interfaces. The configuration of the components is realized using the theory of "soft computations" using the Mamdani fuzzy inference algorithm.